SISTEM INFORMASI MANAJEMEN ARSIP SURAT GMKI CABANG SALATIGA BERBASIS WEB DENGAN FRAMEWORK LARAVEL - Elyan Mesakh Kowi; Suprihadi Suprihadi (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
The Indonesian Christian Student Movement (GMKI) is a student organization that was founded on February 9, 1950. GMKI has approximately 90 branches spread throughout the country, including in Salatiga City. As one of the branches, GMKI Salatiga Branch refers to the Internal Working Mechanism (MKI) as a policy document that regulates correspondence procedures within the organization. In its application, the correspondence mechanism is still carried out in a conventional way and has not utilized technology optimally. This study aims to produce a web-based mail archive management information system with the Laravel framework. The author uses a qualitative descriptive approach in writing. The design method in this study uses the prototype method. Then, for testing the system the author uses the black box testing method. The construction of this web-based information system can make it easier for the Branch Management Board (BPC) of GMKI Salatiga Branch in the process of making template letters and digitally filing letters from anywhere as long as they are connected to the internet.